Upper Jurassic travertine at El Macanudo, Argentine Patagonia: a fossil geothermal field modified by hydrothermal silicification and acid overprinting - Guido, Diego Martin (2017)
The Deseado Massif hosts numerous Late Jurassic (150 Ma) fossil geothermal systems related to an extensive volcanic event developed in a diffuse extensional back-arc setting. Detailed mapping, petrography and mineralogical observations of El Macanudo outcrops verify that it represents a hot-spring-related travertine partially replaced by silica and delineated by six sedimentary facies. These are large concentric cones (F1), laminated vertical columnar structures (F2), porous layers (F3), shrubby and irregular lamination (F4), low-amplitude wavy bedding (F5) and mounds and breccias (F6). The Macanudo Norte Outcrop rocks constitute a silica-replaced travertine sequence, with development of large conical stromatolites in a deep pool or geothermally influenced shallow lacustrine environment, surrounded by a subaerial travertine apron terrace; whereas, the Macanudo Sur Outcrop is a subaerial travertine mound sequence. Structurally controlled vent areas occur in both northern (F1) and southern (F6) outcrops, mainly located along regional NNE- and ENE-trending faults. The other sedimentary units display a concentric distribution of travertine facies with respect to the interpreted vent areas. The El Macanudo palaeo-hot spring deposit is situated in an eroded Jurassic volcanic centre, and records a complex evolutionary-fluid history. The sediments archived three different Jurassic events, when large and long-lasting hydrothermal systems were active across the region. This relative temporal sequence was formed by: (1) travertine precipitation; (2) development of a silica cap, where early silicification was responsible for exceptional preservation of some stromatolitic fabrics; and (3) acid alteration, recorded by dissolution textures and clay formation, and caused by a palaeo-phreatic water-level drop.